2014
DOI: 10.1177/1471301214520780
|View full text |Cite
|
Sign up to set email alerts
|

Facilitating independence: The benefits of a post-diagnostic support project for people with dementia

Abstract: Providing support in the form of information, advice and access to services or social events is promoted as beneficial for people newly diagnosed with dementia and their families. This paper reports on key findings from an evaluation of a post-diagnostic support pilot project in Scotland addressing local service gaps, namely information provision, emotional and practical support and maintaining community links. Twenty-seven participants (14 people newly diagnosed with dementia and 13 family carers) were interv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
26
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 34 publications
(29 citation statements)
references
References 16 publications
3
26
0
Order By: Relevance
“…Giving those diagnosed written information on social care and voluntary services could be best practice on the part of DMP (Lecouturier et al, ) and may be regarded by some GPs as a sufficient response to social need (White et al, ). In contrast, in this study, two participants reported being given inappropriate advice pamphlets aimed at carers, a finding that echoes other research (Kelly & Innes, ; Mountain & Craig, ), and which reflects a potential structural oppression whereby people with dementia are underestimated and perceived as lesser or diminished. Potential strengths and capabilities, often intact at early stages (Yale, ), are ignored.…”
Section: Discussionsupporting
confidence: 67%
See 4 more Smart Citations
“…Giving those diagnosed written information on social care and voluntary services could be best practice on the part of DMP (Lecouturier et al, ) and may be regarded by some GPs as a sufficient response to social need (White et al, ). In contrast, in this study, two participants reported being given inappropriate advice pamphlets aimed at carers, a finding that echoes other research (Kelly & Innes, ; Mountain & Craig, ), and which reflects a potential structural oppression whereby people with dementia are underestimated and perceived as lesser or diminished. Potential strengths and capabilities, often intact at early stages (Yale, ), are ignored.…”
Section: Discussionsupporting
confidence: 67%
“…The diagnostic process should not be a one‐off event (Dhedhi et al, ; Aminzadeh, Byszewski, Molnar, & Eisner, ; Koch & Iliffe, ): there should be more than one appointment to discuss diagnosis and enable effective care planning (Kelly & Innes, ). This could involve the outlining of appropriate support services that community and voluntary agencies provide.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations